Evaluation of solid-state bioconversion of domestic wastewater sludge as a promising environmental-friendly disposal technique - Molla , Abul Hossain; Fakhru’l-Razi, Ahmadun; Alam, Md. Zahangir (Elsevier Science, 2004)
Natural and environmental-friendly disposal of wastewater sludge is a great concern. Recently, biological treatment has played prominent roles in bioremediation of complex hydrocarbon- rich contaminants. Composting is quite an old biological-based process that is being practiced but it could not create a great impact in the minds of concerned researchers. The present study was conducted to evaluate the feasibility of the solid-state bioconversion (SSB) processes in the biodegradation of wastewater sludge by exploiting this promising technique to rejuvenate the conventional process. The Indah Water Konsortium (IWK) domestic wastewater treatment plant (DWTP) sludge was considered for evaluation of SSB by monitoring the microbial growth and its subsequent roles in biodegradation under two conditions:(i) ﬂask (F) and (ii) composting bin (CB) cultures. Sterile and semi-sterile environments were allowed in the F and the CB, respectively, using two mixed fungal cultures, Trichoderma harzianum with Phanerochaete chrysosporium 2094 (T/P) and T. harzianum with Mucor hiemalis (T/M) and two bulking materials, sawdust (SD) and rice straw (RS). The signiﬁcant growth and multiplication of both the mixed fungal cultures were reﬂected in soluble protein, glucosamine and color intensity measurement of the water extract. The color intensity and pH of the water extract signiﬁcantly increased and supported the higher growth of microbes and bioconversion. The most encouraging results of microbial growth and subsequent bioconversion were exhibited in the RS than the SD. A comparatively higher decrease of organic matter (OM) % and C/N ratio were attained in the CB than the F, which implied a higher bioconversion. But the measurement of soluble protein, glucosamine and color intensity exhibited higher values in the F than the CB. The ﬁnal pH drop was higher in the CB than the F, which implied that a higher nitriﬁcation occurred in the CB associated with a higher release of H+ ions. Both the mixed cultures performed almost equal roles in all cases except the changes in moisture content.